Effect of Aerobic Exercise on Lipid Metabolism in Rats With NAFLD - Zhou, Tongxi; Niu, Mengfan; Liu, Ruichen; Li, Li (Frontiers in Genetics, 2022)
To attempts the intervention effect of exercise on lipid metabolism in NAFLD rats, provide a more scientific experimental basis for exploring and improving the theoretical system of exercise intervention in NAFLD, and further provide a theoretical research basis for clinical treatment of NAFLD. Forty healthy male sprague-dawley rats were randomly divided into blank control group (BC,14) and model group (MO，26). After 6 weeks of modeling, the MO group was randomly divided into model control group (MC, 12) and aerobic exercise group (AE, 12). Platform running intervention in group E was conducted at a slope of 0 degree, a speed of 15 m/min, 1 hour/time, once a day, 6 times a week, and a day of rest, for 8 weeks in total. After the intervention, the liver tissues of rats were taken for pathological sections, serum were taken and analyzed for TC, TG, LDL-C, HDL-C,FFA and leptin levels.